Development Of Betacyanin Pigment Extract And Microencapsulated Powder From Red Pitaya Fruit (Hylocereus Polyrhizus) - Ruri , Aditya Sari (2011)

(untitled)
Betacyanin pigments from red pitaya fruit (Hylocereus polyrhizus) could be an attractive source of natural red colourant for food application. The extraction of betacyanin pigment was extracted from the flesh and peels of red pitaya fruits grown locally in Malaysia by using acetone, methanol and water as the extracting solvents. Both the flesh and peels were investigated and it was found that the flesh had higher of pigment contents compared to the peels (10.14  0.57 and 6.69  0.21 mg of betanin equivalents, (BE)/100 g, respectively). Based on the betacyanin content, the pigment extract with water extraction obtained from red pitaya fruit flesh was selected for further study.